Membrane-permeable tenofovir-di- and monophosphate analogues - Jia, Xiao; Kullik, Giuliano A; Bufano, Marianna; Brancale, Andrea; Schols, Dominique; Meier, Chris (European journal of medicinal chemistry, 2024)
The development of new antiviral agents such as nucleoside analogues or acyclic nucleotide analogues (ANPs) and prodrugs thereof is an ongoing task. We report on the synthesis of three types of lipophilic triphosphate analogues of (R)-PMPA and dialkylated diphosphate analogues of (R)-PMPA. A highly selective release of the different nucleotide analogues ((R)-PMPA-DP, (R)-PMPA-MP, and (R)-PMPA) from these compounds was achieved. All dialkylated (R)-PMPA-prodrugs proved to be very stable in PBS as well as in CEM/0 cell extracts and human plasma. In primer extension assays, both the monoalkylated and the dialkylated (R)-PMPA-DP derivatives acted as (R)-PMPA-DP as a substrate for HIV-RT. In contrast, no incorporation events were observed using human polymerase γ. The dialkylated (R)-PMPA-compounds exhibited significant anti-HIV efficacy in HIV-1/2 infected cells (CEM/0 and CEM/TK-). Remarkably, the dialkylated (R)-PMPA-MP derivative 9a showed a 326-fold improved activity as compared to (R)-PMPA in HIV-2 infected CEM/TK- cells as well as a very high SI of 14,000. We are convinced that this study may significantly contribute to advancing antiviral agents developed based on nucleotide analogues in the future.
Keywords: Adenine; nukleotidy; Anti-HIV Agents; adenin; Nucleoside; Reverse transcriptase; Organophosphonates; Prodrugs; Humans; HIV-2; Tenofovir; prekurzory léčiv; Antiviral compounds; látky proti HIV; DNA polymerase; Triphosphate; Prodrug; tenofovir; organofosfonáty; Nucleotides; lidé